The Influence of Brand Equity, Product Quality And Social Responsibility Marketing on The Efficiency Of The Electrical And Electronics Industry in Thailand - Kuakudling, Pitsanu; Luanchumroen, Somchit; Fongsuwan, Wanno; Chinundech, Norapol; Duangkae, Somsunee (Journal of Multidisciplinary Academic Research and Development (JMARD), 2020)
The research purpose was studied factors that affect to Organizational Performance of Electrical Appliance and Industries in Thailand. Research was quantitative research and questionnaires were constructed to be a tool to measure concept definition and data were collected from 342 people. The data was analyzed by multiple regression analysis. The study found that factors high positively affecting to Organization Performance of Electrical Appliance and Industries in Thailand were Product Quality and Social Responsibility Marketing ( = 4.18, 4.18 respectively) and Brand Equity ( = 4.15), the significance level .05. The relationship of factors could explain the variation of organizational efficiency to 90.40 percent (R2 = .904).